Ecological effects of impoundments in the Buffalo River, Eastern Cape, with particular reference to the distribution of blackflies (Diptera : simuliidae) - Palmer, Robert William (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1992)
This thesis examines the extent and intensity of the effects of impoundments on selected physical, chemical and biotic conditions in an impounded southern African river. Life-history characteristics and environmental requirements which determine the success of impoundment-outlet blackflies in southern Africa were studied. Difficulties with the identification of immature blackflies led to a search for additional diagnostic characters, the description of larvae of seven species previously unknown, and the development of new keys to the species of Simulium (larvae and pupae) in southern Africa. Distribution records for each species are presented, and their ecology is summarised. Three pairs of closely related species, which were formerly indistinguishable, can now be recognised by differences between the structure of their cephalic fan microtrichia. Monthly physical, chemical and invertebrate samples at 16 sites upstream and downstream of four impoundments in the Buffalo River, eastern Cape, were taken over a period of two years. The downstream effects of impoundments on these parameters depended on the variable examined, the position of the impoundment along the river profile, the depth from which water was released, and the quality of the inflowing water. Impoundments in the Buffalo River caused an upstream shift of the thermal and suspended organic conditions, and the distribution of blackfly species. Surface-release impoundments in the clean, upper-reaches of the river caused increases in water temperature (by as much as 8ºC) and chlorophyll a (by as much as 600%). Recovery to riverine conditions was within 2.6 to 18.4 km, depending on flow. A polluted, surface-release impoundment in the middle-reaches of the river had a slight dampening effect on river temperatures, converted the particle size spectrum of the river from small (<80 μm) to large (250-1000 μm), and improved the water quality of the downstream reaches (with the exception of nitrate concentrations, which were higher in the tailwaters compared to inflowing water). An impoundment in the lower reaches caused reductions in maximum temperature of up to 6ºC when releasing water from the surface, and up to 16ºC when releasing water from the bottom. Bottom-released water carried high concentrations (36 to 190 g m³) of small (<5 μm) and largely inorganic (86 to 93%) material.Twenty species of blackflies were found in the Buffalo River, of which 18 were distinguishable as larvae. They were divided into those which were widespread (5 taxa), those restricted to waterfalls and mountain torrents (2 taxa), those found in the foothill stony run zone (6 taxa), and rare taxa (5 taxa). Impoundments in the Buffalo River did not alter population densities of blackfly larvae, but did alter blackfly species composition, favouring five species commonly found in mid-order streams in southern Africa (s. meduseaforme, S. hargreavesi, S. nigritarse, S. adersi and s. damnosum s.l.) at the expense of upper-reach species (s. rutherfoordi, S. letabum and s. impukane). These five species are regarded as typical of impoundment-outlets, and were small, multivoltine flies whose larvae shared a generalised cephalic fan microtrichial structure, consisting of a single row of moderately differentiated microtrichia. A strong relation was found between cephalic fan microtrichial structure and larval habitats: Taxa found in fast-flowing, clear water had a more complex fan structure compared to those found in slow-flowing, turbid water. It is concluded that impoundment-induced changes to hydrodynamics and transported material (food) are important factors which have changed the distribution of blackflies in southern Africa in recent times. These changes are more severe downstream of upper-reach impoundments than middle or lower-reach impoundments.
Keywords: Stream ecology -- South Africa -- Buffalo River (Eastern Cape); Dipter -- South Africa -- Buffalo River (Eastern Cape)